(untitled) (Development Service Industry Management, 2025)
The article discusses integrating marketing strategies into a company’s supply chains as a key factor in enhancing operational efficiency in a dynamic external environment. The instability of market processes, intensifying crises, demand uncertainty, and internal imbalances between functional units make it impossible to apply traditional logistics management approaches without considering marketing priorities. The study substantiates the need for a strategic alignment of marketing and logistics activities to achieve synergy in the functioning of the enterprise’s distribution system. The research analyzes the main drivers for the integration of marketing strategies into supply chains: increased competitiveness through consumer orientation; optimization of logistics costs, including transportation, warehousing, and inventory management; reduction of risks associated with demand-supply imbalances through more accurate forecasting based on marketing analytics; shortening of logistics cycles through route and schedule optimization; and the development of stable and predictable distribution channels. The article examines the structure of distribution strategies, which includes the selection of market coverage types (intensive, selective, exclusive), the identification of target segments (differentiated, undifferentiated, concentrated marketing), and intermediary engagement strategies (active, moderate, zero involvement). It is demonstrated that a rational combination of these elements contributes not only to a higher level of customer satisfaction but also ensures the coherence of managerial decisions across the enterprise. The study concludes that integrating marketing strategies into supply chains creates preconditions for strengthening the company’s market position, supporting its long-term development, and improving the overall efficiency of operational activities.